Pengaruh Teamwork, Disiplin Kerja, dan Iklim Organisasi terhadap Kinerja Karyawan: Studi di Rumah Sakit X Jakarta Selatan - Latifah Intan Safitri; Renny Husniati; Yul Tito Permadhy (Studi Ilmu Manajemen dan Organisasi, 2021)
Purpose: The purpose of this study was to determine, prove and analyze the effect of teamwork, work discipline, and organizational climate on employee performance at X Hospital, South Jakarta. Research Methodology: This research is a quantitative research by making permanent employees of Hospital X as many as 187 people as the population with a non-probability sampling technique using convenience sampling, based on the solving formulas, a sample of 130 respondents was obtained. Data processing used IBM SPSS Statistics 23 program with a significance level of 5% (0.05). Results: The results show that teamwork partially has an influence on employee performance, work discipline partially has an influence on employee performance, organizational climate partially has an influence on employee performance, simultaneous teamwork, work discipline, and organizational climate influence employee performance. Limitations: In the process of collecting data, researchers cannot directly see and assist respondents in completing the research because the health protocol implemented at hospital X south Jakarta during the covid-19 pandemic is very strict. Contribution: It is hoped that this research can provide meaning and material for consideration to achieve increased performance in accordance with industry expectations and goals. And hoped that this research can provide positive benefits so that employees are motivated to maintain order and teamwork in carrying out their duties to improve employee performance.